Identification of protein biomarkers for candida parapsilosis and candida tropicalis - Lee, Pey Yee (2014)
Candida species are the major human fungal pathogens and incidence of systemic candidiasis has been rising over the years with Candida albicans as the main species isolated. However, Candida parapsilosis and Candida tropicalis have emerged recently as increasingly prevalent pathogens, but only few studies have focused on them thus far. In the first part of this study, systemic infection of C. parapsilosis and C. tropicalis were generated in mice via intravenous challenge and their pathogenicity was studied. It was demonstrated that mice challenged with C. parapsilosis and C. tropicalis exhibited different survival rate, with death only observed for C. tropicalis-infected mice. Besides, C. tropicalis-infected mice displayed higher fungal tissue burden and more severe kidney damage. Overall, the results indicate that C. tropicalis was more virulent than C. parapsilosis and suggests that specific virulence factors such as morphogenesis may account for variation in pathogenesis. In another context, difficulty in establishing definitive diagnosis for candidasis has prompted the search of biomarkers for the disease. Squalene synthase is a novel antigenic protein of C. tropicalis that was discovered from a previous study. To investigate its potential as a biomarker candidate, this protein was expressed in Pichia pastoris and the fusion protein was purified by affinity chromatography. The results showed that the purified recombinant protein was specifically recognized by polyclonal antibodies from C. tropicalis-infected mice on Western blot, suggesting that the protein could be a potential biomarker for C.tropicalis. However, further testing is needed to confirm its utility. To further discover protein biomarkers for C. parapsilosis and C. tropicalis and to understand their host-pathogen interactions, an immunoproteomic analysis was performed. For this purpose, cell wall proteins-enriched fractions of C. parapsilosis and C. tropicalis were systemically screened for antigens using antisera obtained from experimentally infected mice. This analysis led to the identification of 12 immunogenic proteins each for C. parapsilosis and C. tropicalis, of which 8 were common antigens for both species. Among these antigens, 14 have been previously reported as antigens of C.albicans, whereas isocitrate dehydrogenase (Idh2p) and dihydrolipoyllysine-residue succinyltransferase (Kgd2p) were novel immunogenic proteins that were reported for the first time for Candida species. The present work showed that these antigens were expressed in vivo during infection and are likely to play important roles in pathogenesis. Next, the newly reported antigens, Idh2p and Kgd2p were overexpressed as recombinant proteins in Escherichia coli and subsequently purified by affinity chromatography. The antigenicity of the recombinant proteins was verified by immunoblotting using antisera from infected mice. This preliminary work suggests that the two proteins may find potential application as biomarker for C.parapsilosis and C. tropicalis. However, additional work is required to evaluate the usefulness of these proteins. Collectively, findings from the mouse model of infection and antigen profiling by immunoproteomics help to improve understanding on host response to C. parapsilosis and C. tropicalis infection, as well as discovering new protein antigens to be employed as disease biomarker candidates. This work also described the production of several antigenic recombinant proteins that lays the foundation for further research.